Long-Term Retention Rate of Golimumab in Patients With Rheumatoid Arthritis, Psoriatic Arthritis, and Spondyloarthritis in a Real-Life Setting. Issue 1 (25th January 2021) - Serrano-Benavente, Belén; Valor, Larissa; del Río Blasco, Tamara; Janta, Iustina; González Benítez, Roberto; Nieto-González, Juan Carlos; Martínez-Barrio, Julia; Ovalles Bonilla, Juan Gabriel; Ariza, Alfonso; López-Longo, Francisco Javier; Álvaro-Gracia, Jose María; Monteagudo, Indalecio; et al.
Objective: The aims of this study were to describe the long-term retention rate of golimumab (GLM) treatment in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and spondyloarthritis (SpA) in real life, and to analyze determinants of discontinuation. Methods: We conducted a single-center, medical records review study of all patients with RA, PsA, and SpA on GLM treatment attending a large rheumatology department from 2010 to 2017. Times from start to end of GLM treatment were collected, as well as sociodemographic, clinical, and safety variables. Golimumab retention rate was estimated by the Kaplan-Meier method, and comparison across diseases was analyzed with the Mantel-Haenszel statistic (log-rank test). Cox proportional hazards regression models were used to identify factors associated with GLM discontinuation. Results: In the study period, a total of 212 patients (61 RA, 48 PsA, 103 SpA) were prescribed GLM. Retention rates were 72% in the first year, 61% in the second, 56% in the third, and 38% at 5 years. Differences were statistically significant across diseases (median times to GLM discontinuation were 50.2, 46.0, and 38.7 months for RA, SpA, and PsA, respectively) and according to the number of previous biologic therapies (55.2 months in biologic-naive patients vs 14.0 months in patients with ≥2 previous biologics; p < 0.001). The use of concomitant conventional synthetic disease-modifying antirheumatic drugs was associated with a lower probability of discontinuation (hazards ratio [HR], 0.57; 95% confidence interval [CI], 0.33–0.97). Female sex (HR, 1.84; 95% CI, 1.07–3.17) and having used 2 biologics before GLM (HR, 2.99; 95% CI, 1.76–5.06) were associated with increased discontinuation rates. Twenty-three patients (10.9%) had at least 1 serious adverse event. Conclusions: In a real-life setting, GLM shows appropriate long-term safety-effectiveness ratio.